1999
DOI: 10.1111/j.1469-7793.1999.0101o.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat supraoptic magnocellular neurones show distinct large conductance, Ca2+‐activated K+ channel subtypes in cell bodies versus nerve endings

Abstract: Rat magnocellular neurones with cell bodies in the supraoptic and paraventricular nuclei of the hypothalamus send their axonal nerve endings into the neurohypophysis, where they release oxytocin or vasopressin into the bloodstream during highly specific firing patterns. Peptide release from the neurohypophysis is closely controlled by an interplay between the duration and frequency of the action potential burst, and the silence that separates the bursts generated by these neurones (Cazalis et al. 1985). Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
89
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 46 publications
15
89
0
Order By: Relevance
“…Earlier findings indicated that the acute actions of ethanol differ between cellular compartments of magnocellular neurons, with BK channels located in the terminals potentiated by ethanol, whereas BK channels in the cell bodies were insensitive to ethanol (Dopico et al, 1999b). Single-channel recordings showed that the acute actions of ethanol targeted the gating of the channels: the contribution of long openings to the total time spent in the open Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier findings indicated that the acute actions of ethanol differ between cellular compartments of magnocellular neurons, with BK channels located in the terminals potentiated by ethanol, whereas BK channels in the cell bodies were insensitive to ethanol (Dopico et al, 1999b). Single-channel recordings showed that the acute actions of ethanol targeted the gating of the channels: the contribution of long openings to the total time spent in the open Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…1, the model contains several voltage-gated currents: the transient voltage-gated sodium current (I Na ) (Tanaka et al 1999), the delayed rectifier potassium current (I K(DR) ) , the A-type transient potassium current (I A ) , and L-and Ntype Ca 2+ currents (I Ca,L , I Ca,N ) (Foehring and Armstrong 1996;Joux et al 2001). It also contains the following Ca 2+ -dependent currents: a K + current mediated by large conductance K + (BK) channels (Dopico et al 1999), a K + current mediated by small conductance K + (SK) channels (Kirkpatrick and Bourque 1996), a non-selective cation (CAN) current (I CAN ) (Ghamari-Langroudi and Bourque 2002), and a slowly activated K + current in OT neurons Armstrong 1995,1997).…”
Section: 12mentioning
confidence: 99%
“…Activation of the SK channels is voltage independent and highly sensitive to intracellular Ca 2+ (Hille 2001;Sah and Davies 2000); BK channel activation is both voltage-and Ca 2+ -dependent (Vergara et al 1998;Dopico et al 1999). While activation of BK channels contributes to the falling phase of individual action potentials and the generation of the fast after hyperpolarizing potential (AHP) or hyperpolarizing after potential in many types of neurons (Lancaster and Adams 1986;Lancaster and Nicoll 1987;MacDermott and Weight 1982;Womack and Khodakhah 2002), including MNCs (Dopico et al 1999), SK channel activation is responsible for the generation of the AHP following a train of action potentials (Armstrong et al 1994;Bourque and Brown 1987;Greffrath et al 1998;Kirkpatrick and Bourque 1996;Lancaster and Adams 1986;Lancaster and Nicoll 1987;Sah and Bekkers 1996). This apamin-sensitive AHP is intermediate between the fast AHP (~50 ms) and "slow" AHP (lasting >5 s) (GhamariLangroudi and Bourque 2004).…”
Section: (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, EtOH inhibition of BK channels is not universal, because both channel activation (18,19) and refractoriness (20) were observed. EtOH action on BK channels varies amongst slo subunit isoforms (21), cell domains (20), and bilayer lipid species (19). Thus, EtOH action on channels heterologously expressed may differ dramatically from drug action on the native channel studied in intact cerebrovascular myocytes.…”
mentioning
confidence: 99%